Handbook of rigging for construction and industrial operations - Rossnagel, W. E (McGraw Hill, 1988)
Providing coverage of relevant OSHA regulations and the advice on safe practices, this guide shows you how to select and use rigging tools-fiber and wire-strand rope, slings and hitches, end attachments and fittings, and blocks. It also shows you how to use sheaves, reeving, and drums-scaffolding and ladders, both manual and swinging scaffolds.